The Influence of Organizational Culture and Leadership Style on Employee Performance With Social Interaction as an Intervening Variabel at PT. Bank Pembangunan Daerah Jambi - Zulfikar Zulfikar; Osrita Hapsara; Ali Akbar (Dinasti International Journal of Management Science, 2023)
The purpose of this study was to describe organizational culture, leadership style, social interaction and employee performance at PT Bank Pembangunan Daerah Jambi, then to analyze the influence of organizational culture and leadership style on social interaction, analyze the influence of organizational culture and leadership style on employee performance, then analyze the influence of social interaction on employee performance, then analyze the influence of organizational culture and leadership style through social interaction on employee performance. This research using descriptive and verification research methods, namely a method for researching a group of people, an object, situation and condition of a system of thought with the aim of creating a description, a systematic picture according to the facts being investigated. The verification research aims to test the hypothesis about the influence of the variables in this study. This research involved 226 employees at PT Bank Pembangunan Daerah Jambi. The sample was 70 respondents based on the Slovin formula with a confidence level of 1%. Data were analyzed using SPSS.22. The results showed that organizational culture was really good, leadership style was in high performance, social interaction and employee performance was also high, that organizational culture and leadership style simultaneously or partially had a positive and significant effect on social interaction, organizational culture and leadership style simultaneously and partial positive and significant effect on employee performance, and social interaction has a positive and significant effect on employee performance at PT Bank Pembangunan Daerah Jambi. To be able to improve customer service, the attitude of appreciating the contribution of each employee, building public trust and becoming a positive role model, and improving the quality of digital services are demands that must be met. If considered in term of management to provide motivation and inspiration, it can be done by applying reward rules to employees who have good performance achievements beyond the targets that have been set and punishing employees who violate the rules.